The Analysis of Miracle in A Film of Noah 2014: in Mysticism Context - Qesha Adrian Ashiddiq; Bahar Bahar; Ibnul Qayyim (DEIKTIS: Jurnal Pendidikan Bahasa dan Sastra, 2025)
Mysticism is a field that deeply connected with religious beliefs or spiritual experiences, mysticism has been used in many literary works such as film to increase the appeal of the literary works. This research is aimed to; (1) Find types of mysticism that contained in the Film of Noah 2014; (2) How mysticism portrayed in the film. The data used in the study came from the film of Noah 2014. The data is in form of cut scene that contain the mysticism phenomenon. The instrument of this research contains qualitative descriptive analysis, mysticism theory by Walter T. Stace as an analysis tool, and note taking technique as data collecting instrument. The data will be collected by watching the film several times and taking notes and pictures of the scene that contains mysticism phenomenon. The result of the analysis showed that there are two types of mysticism phenomenon that occurred in the film and it was portrayed as several miracles that happen around Noah as the Main character of the film.